2009
DOI: 10.1021/om900018y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Substituent Effects of Binuclear Ruthenium Vinyl Complexes [RuCl(CO)(PMe3)3]2(μ-CH═CH−Ar−CH═CH)

Abstract: A series of binuclear ruthenium vinyl complexes [RuCl(CO)(PMe 3 ) 3 ] 2 (µ-CHdCH-Ar-CHdCH) (Ar 6l), and C 6 H 3 CF 3 (6m)) have been prepared. The respective products have been characterized by elemental analyses, NMR spectrometry, and UV/vis spectrophotometry. The structures of 6h, 6i, and 6j have been established by X-ray crystallography. Electrochemical studies have revealed that intermetallic electron communication between the two Ru centers may be fine-tuned by modification of the bridging spacers, that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 146 publications
2
40
0
Order By: Relevance
“…Our previous study on [RuCl (CO)(PMe 3 ) 3 ] 2 (CH=CHC 6 H 4 CH=CH) compounds revealed that each methyl substituent increases DE p by about 4mVt hrough modification of 1,4-diethenylphenylene bridging ligand. [63,64] Thus, from the potentials hift induced only by the torsion angle of the biphenyl core, one can estimate that the DE p values should be about 181, 166, 127, 68, and 65 mV for complexes 4a-e,respectively.According to theory,the orbitaloverlap of adjacent p systems correlates linearly with the cos f value, and the electron transmission is proportionalt o cos 2 f. [65] As shown in Figure 3, the potential differences between the first and second redox peaks DE p exhibit am oderately good linear correlation with cos 2 f (R 2 = 0.973). An intercept of about 64 mV was obtained for the situation in which very little or no communication exists between the two ruthenium units (f= 908).…”
Section: Electrochemistrymentioning
confidence: 99%
“…Our previous study on [RuCl (CO)(PMe 3 ) 3 ] 2 (CH=CHC 6 H 4 CH=CH) compounds revealed that each methyl substituent increases DE p by about 4mVt hrough modification of 1,4-diethenylphenylene bridging ligand. [63,64] Thus, from the potentials hift induced only by the torsion angle of the biphenyl core, one can estimate that the DE p values should be about 181, 166, 127, 68, and 65 mV for complexes 4a-e,respectively.According to theory,the orbitaloverlap of adjacent p systems correlates linearly with the cos f value, and the electron transmission is proportionalt o cos 2 f. [65] As shown in Figure 3, the potential differences between the first and second redox peaks DE p exhibit am oderately good linear correlation with cos 2 f (R 2 = 0.973). An intercept of about 64 mV was obtained for the situation in which very little or no communication exists between the two ruthenium units (f= 908).…”
Section: Electrochemistrymentioning
confidence: 99%
“…ν(CO) Values (cm −1 ) for the Complexes Ru(CO)(L)(P i Pr 3 ) 2 (CHCHC6 H 4 R-4) and Their Radical Cations…”
mentioning
confidence: 99%
“…The two double bonds are in a trans configuration. The overall geometry of complex 1 closely resembles those of the bimetallic ruthenium complexes [RuCl(CO)(PMe 3 ) 3 ] 2 (l-CH@CH-Ar-CH@CH) [35,42]. …”
Section: Description Of the Structurementioning
confidence: 77%